Penggunaan Media Pembelajaran Untuk Meningkatkan Pemahaman Listrik Magnet Bagi Siswa Di Sd Negeri Taman Sari 1 Pulomerak - Siti Hanan; Asih Setyorini; Irfan Muhammad (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The use of learning media is something that can provide an understanding of the concept of electricity in everyday life. The place of service is held at Taman Sari 1 Pulomerak State Elementary School. In the world of education in the current era, learning media can be an alternative teaching aid that is visually easy for students to understand. The implementation of community service consists of preparation, planning, implementation, and evaluation. As a result of this dedication, students learn enthusiastically in studying science in the form of magnetic electricity, where in everyday life magnetic electricity is always found. Training on the use of learning media is also expected to make teachers in elementary schools able to apply learning media in improving students' abilities in schools to make them more interactive and fun.